Thermal and strength performance of reinforced self-compacting concrete slabs mixed with basalt and PVA fibers in high intensity fire - Mohd Jani, N. (EDP Sciences, 2017)
Fibers addition to concrete and the innovation of self-compacting concrete technology lead to the development of high-performance concrete. However, high intensity fire may adversely affect the performance of this type of concrete. A series of fire resistance test experiments to evaluate the performance of fiber reinforced self-compacting concrete (FR-SCC) slabs consisting of various mix of basalt and PVA fibers were carried out by subjecting the concrete slabs as an element of construction to high intensity Hydrocarbon fire heating condition. The fire testing condition was in accordance with the standard time-temperature fire curve for 120 minutes up to 1100°C heating temperature. The temperatures on the surface and within the concrete slabs were recorded and the performance of each type of FRSCC slabs were evaluated. The performance of Basalt FR-SCC was found to be more resistant to fire in comparison to PVA FRSCC. There residual compressive strength of core samples were tested and SEM analysis were carried out to determine the effect of high intensity fire on the basalt and PVA FR-SCC slabs. © The authors, published by EDP Sciences, 2017.